2014
DOI: 10.4238/2014.april.17.4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of catechol-O-methyltransferase val(158)met polymorphism in Saudi schizophrenia patients

Abstract: ABSTRACT. Schizophrenia is a complex neuropsychiatric disorder strongly associated with dopamine dysregulation. Catechol-O-methyltransferase (COMT) is a candidate gene for schizophrenia that encodes an enzyme involved in the metabolic inactivation of dopamine. The COMT Val 158 Met polymorphism has been associated with schizophrenia and has significant inter-and intra-ethnic variations. We examined a possible association between the COMT Val 158 Met polymorphism and schizophrenia in Saudis, taking into account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…The results pertaining to COMT gene variant were similar to those of the studies done on Asian populations reported in Korea ( 27 ), Taiwan ( 28 ) and France ( 13 ). However, in other ethnic Asian populations, such as Saudi Arabia ( 31 ), India ( 32 ), China ( 30 ) and Turkey ( 29 ), a significant association has been reported between genotype and allotype frequencies in schizophrenia group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The results pertaining to COMT gene variant were similar to those of the studies done on Asian populations reported in Korea ( 27 ), Taiwan ( 28 ) and France ( 13 ). However, in other ethnic Asian populations, such as Saudi Arabia ( 31 ), India ( 32 ), China ( 30 ) and Turkey ( 29 ), a significant association has been reported between genotype and allotype frequencies in schizophrenia group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…(25) S-Al-Asmary, et al in 2014 on the Arab population. (26) Research conducted by EM Sutrisna, 2016 on Javanese, (27)…”
Section: Such Variations Could Affect the Biological Functionsmentioning
confidence: 99%
“…The Val158Met substitution is a functional polymorphism in which the Met allele has 3-4-fold reduced COMT activity resulting in lower levels of neurotransmitter degradation and higher levels of transmitter availability [ 26 ]. The ancestral Val allele has been reported in control populations at highest frequencies in Asians (69–80%) and lower frequencies in Caucasians (46–60%), North Africans (50–80%), and Arabs (44–50%) [ 27 30 ]. COMT is located in a region of chromosome 22 that was implicated in the pathogenesis of schizophrenia in early linkage analysis studies so many COMT studies have focused on its association with schizophrenia and related risk factors like stress and drug use [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%